2010
DOI: 10.1088/1751-8113/43/44/445302
|View full text |Cite
|
Sign up to set email alerts
|

Correlation function and mutual information

Abstract: Correlation function and mutual information are two powerful tools to characterize the correlations in a quantum state of a composite system, widely used in many-body physics and in quantum information science, respectively. We find that these two tools may give different conclusions about the order of the degrees of correlation in two specific two-qubit states. This result implies that the orderings of bipartite quantum states according to the degrees of correlation depend on which correlation measure we adop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Mainly, we consider correlation and independence information. These concepts have profound implications in the physical [ Dong and Zhou , 2010; Peleg et al , 2010] and information science fields [ Cover and Thomas , 2006; Papoulis , 1991]. We shortly describe these concepts for efficiently combine multimodel ensemble data.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Mainly, we consider correlation and independence information. These concepts have profound implications in the physical [ Dong and Zhou , 2010; Peleg et al , 2010] and information science fields [ Cover and Thomas , 2006; Papoulis , 1991]. We shortly describe these concepts for efficiently combine multimodel ensemble data.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Mainly, we consider correlation and independence information. These concepts have profound implications in the physical [Dong and Zhou, 2010;Peleg et al, 2010] and information science fields The last column (FOEX) gives the percentage of over-prediction (>0) or under-predictions (<0). In the next to last row, Median Model results, averaged over models from m01 to m16 (following Galmarini et al [2004b]) are shown.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, by analogy with the concept of correlation functions for describing correlation effects in many-body physics [28] and taking into account that correlation functions are directly related to observables [28], it can be verified that the information related to both, classical and quantum correlations present in the composite quantum system, is in fact contained inside the elements T ij of the correlation matrix T. This matrix was used to investigate, for example, the dynamics of open quantum systems in the presence of initial correlations [29], and to study correlations in the quantum state of a composite system [30,31].…”
Section: A Quantum Discordmentioning
confidence: 99%
“…QMI has various appealing properties and also admits diverse operational interpretations, e.g., as the amount of noise required to completely destroy all correlations [27][28][29]. Notwithstanding, there also exist observations showing incompatibilities between some measures of the total, classical, and quantum correlations [30][31][32][33] as opposed to what had been largely accepted, which indicate that QMI or other mea-sures of entanglement and quantumness of correlations may not be compatible for ordering quantum states based on the amount of correlations they contain [34]. In a broader context, it has been known in (quantum) resource theory that some resources are not totally ordered sets; see, e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%